Building healthy eating habits in childhood: a study of the attitudes, knowledge and dietary habits of schoolchildren in Malaysia - Kazi Enamul Hoque; Megat Ahmad Kamaluddin; Ahmad Zabidi Abdul Razak; Afiq Athari Abdul Wahid (PeerJ, 2016)
Background Overweight and obesity have increased rapidly in incidence to become a global issue today. Overweight and obesity problems are significantly linked to unhealthy dietary patterns, physical inactivity and misperception of body image. This study aimed to determine whether Malaysian children build healthy eating habits from childhood. Methods A survey on eating habits was conducted among primary school students in standards 4 to 6 in the state of Selangor, Malaysia. The findings of the study were reported in the form of descriptive statistics involving frequencies and percentages. Data from 400 respondents were analyzed. Results Our findings showed that the students understood the definition of healthy food and the types of food that are considered healthy. Although the students knew that food such as deep-fried drumsticks and hamburgers contain a high amount of saturated fat and cholesterol, these foods were still consumed by them. There was also a high consumption of foods that are fried and contain sugar, salt and saturated fat. In choosing food, two major factors contributed to the students’ decisions: cleanliness (65.8%) and the preference of their parents (12.3%). Discussion Our findings indicate that by implementing the Integrated School Health Program (ISHP) properly, students’ eating habits can be improved by creating a school with a healthy environment.